Rule of Law and global power: contemporary challenges for guarantee-based constitutionalism - Ferrajoli, Luigi (2025)
In recent years, Constitutional Law has faced a series of challenges stemming from the advancement of new technologies, the impact of climate change, and transformations in the migration and economic policies of states. These phenomena, in many cases, call into question the role of constitutionalism as a guarantor of rights, especially when domestic policies promote initiatives that weaken the fundamental principles upon which constitutional orders are built.In this context, Dr. Luigi Ferrajoli offers a reflection based on his extensive academic and professional experience. Throughout the interview, he analyzes the relationship between the international political situation and the development of constitutionalism, emphasizing the need to strengthen mechanisms that ensure the effective protection of individuals. He also elaborates on his proposal for a ‘Constitution of the Earth’ as a normative framework aimed at guaranteeing universal rights that transcend state borders. Finally, it expresses concern about the growing prioritization of economic efficiency at the expense of social rights, highlighting the importance of subjecting the power of economic agents to clear legal limits.